Contention therapy induced in manual function in patients affected by stroke: a systematic review (Research, Society and Development, 2020)
This systematic review sought to analyze the influence of contention therapy induced (CTI) on manual function in patients with stroke. The PUBMED, BIREME and SciELO databases were used, with the descriptors: “Stroke” AND “Induced Strain Therapy” AND “Upper Limb”, and their respective correspondents in English. Articles in English and Portuguese, published between 2000 and 2014, which used CTI to improve the manual function of individuals affected by stroke were included. Literature review articles and articles repeated in the databases were excluded. The crossing of descriptors resulted in 380 studies and, after applying the eligibility criteria, 10 articles remained. Studies have found that CTI is able to promote cortical reorganization through intensive and repetitive training of the upper limb compromised by stroke. The authors observed that the technique contributed to improving the function of the compromised upper limb when the therapy was intensive, performed for long periods. The effectiveness of CTI was observed in the short and long term, as long as movements are avoided. Therefore, CTI is a good alternative for the rehabilitation of patients with stroke and who neglect the paretic limb, due to muscle weakness, alteration of tone and other associated factors.